THE USAGE OF SOLAR ENERGY TO REDUCE HOT TEMPERATURE IN THE CAR - Suhaimi, Misha; Herawan, Safarudin Gazali; Md Daud, Nazri (2010)
Park a car under sunlight without any shade for a several hours will cause the temperature in the car increase up to 60 degC to 80 degC depending on the outside temperature. The hot air in a car will make passengers are not comfortable to sit in the car. They have to switch on the air-conditioning and open the car’s window for a several minutes to release the hot air from the car interior space. The hot air will also reduce the life time of the car interior such as a dashboard, seat and interior roof. Normally if the components are exposes to the sunlight frequently the color will change to pale color. The car dashboard, seat and air-freshener emits benzene when expose to high temperature. Actually the heated plastic smell in the car is benzene. The benzene can cause cancer, anemia and reduces white blood cells. The solar energy can be used to generate the electricity and convert to mechanical energy. In this research the electricity will be used to rotate the fan in the car. The fan will remove the hot air and benzene from car interior space to the surrounding through the air conditioning channel. The source of energy that rotated the fan is from solar energy. In other words, there is no additional energy required. There are several experiments have been carried out in this project. The device used are two unit of 12V suction fan which powered by two unit of 12V solar panel. The results show that when a car is installed with the device, it will able to reduce temperature in the range of 2.8% to 7.1 % lower than the temperature of a car without the device. It clearly indicates the positive effect of the device to reduce the temperature of a car when park under hot weather.